Sistem Informasi Distribusi Cabai Dengan Metode Distribution Requirements Planning (DRP) di Provinsi Jawa Timur - Nur Kholis Mansur; Saiful Bukhori; Oktalia Juwita (Faculty of Computer Science, University of Jember, 2019)
Chili production in East Java in 2016 reached nearly 2 million tons with details of 1 million tons of chili and large chili 939 thousand tons. The abundant amount of chili production is still the cause of inflation. The inflation factor is caused by several factors, one of which is the abundant amount of chili production but occurs in certain months or other causes are uneven distribution. The chili production center in East Java is still experiencing problems with distribution activities in meeting the demands of chili every city. Shipments carried out in East Java also do not have an optimal value to meet the number of requests. The poor delivery plan also caused errors in arranging inventory to make deliveries. The East Java government needs a way to analyze the distribution of chili by planning scheduling to improve the ability to fulfill chili demand using the Distribution Requirement Planning (DRP) method. Planning using this DRP method can produce an analysis of the gross needs and needs of chili in each city with the level of service used in the safety stock is 90%, with a normal distribution table that is equal to 1.28.